Tapetum development in transgenic tobacco (Nicotiana tabacum L.) plants with modlfied level of histone H1 variants - Joanna Ślusarczyk; Teresa Tykarska; Andrzej Wierzbicki; Andrzej Jerzmanowski (Acta Societatis Botanicorum Poloniae, 2011)
The phenomenon of male sterility has often been observed in investigations on the role of histone H1 in regulation of morphogenetic and cytological processes in transgenic tobacco plants. These changes were accumulated by disturbances in flower development, consisting in lengthening of the pistil style in relation to stamen heads. This prevented pollination and production of seeds. As similar abnormalities occurred also in the present investigations (depending on combination, the sterility% was 84.4 to 19.9, at only 8.1 in the control), the main problem of our investigations was an attempt to explain their reasons. It is commonly known that one of the conditions for formation of fertile pollen is the properly functioning tapetum. Here, we carried out observations of ultrastructure of anther tapetum control cells in respect of abnormalities which occurred during microsporogenesis of transgenic plants with inactivated expression of two major (A, B) and two minor (C, D) histone H1 variants. The investigations were carried out on the following groups of plants: (1) control group with a full set of histone variants (K), (2) with inactivated A and B variants (-AB); (3) with inactivated A, B, C and D variants (-ABCD), (4) with inactivated C and D variants (-CD). It was found that tapetal development was normal in all the investigated groups of plants, and the sequence of changes was similar as in the control. However, certain ultrastructural differences appeared when tapetum functioned as secretory tissue, and in the degeneration phase. In tapetal cell cytoplasm, with participation of rER, lipid bodies were formed, which, having penetrated to the cell surface and to locules, took part in formation of pollen grain sporoderm. Both in the control and in the remaining combination, excluding -ABCD, these bodies looked similar: they were grey, homogenous and surrounded by black jagged deposits. In -ABCD plants, these bodies were more translucent, slightly rarefied, and not surrounded by the deposits. Moreover, in -CD plants, large lipid deposits were frequently observed between remainders of degraded tapetal cells. They did not occur in the control and the remaining combinations.